Sistem Pendukung Keputusan Pemilihan Anggota Kelompok Tani Terbaik Pada Desa Sinar Semendo Menggunakan Metode (SAW) - Sulastri Sulastri; Resy Anggun Sari; Via Khoirun Nisa (Publikasi Indonesia, 2021)
Farmers can be interpreted as someone whose field of work is farming or it can also be interpreted as someone who is engaged in agricultural business primarily by managing land with the aim of and maintaining crops such as rice, flowers, fruit and others in the hope of obtaining the results of these plants to use alone or sell it to others. This application was created using the SAW (Simple Additive Weighting) method. The basic concept of the SAW method is to find the weighted sum of the performance ratings for each alternative on all attributes. The SAW method can help in the decision making of a case, but calculations using the SAW method only produce the greatest value that will be selected as the best alternative. The calculation will be in accordance with this method if the chosen alternative meets the specified criteria. Using the decision support system for selecting the best Farmer group members in the Sinar Semendo village using the Simple Additive Weigtihng (SAW) method helps Sinar Semendo Village to determine the ranking of Farmer Group members from the results of the specified criteria weights, thus providing additional information when determining a selection. This decision support system is based on a website with PHP programming language and MSQL database for data storage.